Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

CHP4 P2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 30

Learning Outcome

 Analyze problem and propose solutions


 Solving problems using recurrence relation
Outline
 Recurrence Relations
 Applications of Recurrence Relations
 Solving Linear Recurrence Relations
 Homogeneous Recurrence Relations
 Non-homogeneous Recurrence Relations
Introduction
 Recurrence relations play an important roles in the
study of algorithms.
 Complex problem can be solved recursively means to
find a way to break it down into smaller sub-problems
 each sub-problem having the same form as the
original problem. When the process is repeated many
times, the last of the sub-problems are small and easy
to solve
 The solutions of the sub-problems can be woven
together to form a solution to the original problem.
Recurrence Relations
Definition: A recurrence relation for the sequence {an}
is an equation that expresses an in terms of one or
more of the previous terms of the sequence, namely,
a0, a1, …, an-1, for all integers n with n ≥ n0, where n0 is a
nonnegative integer.

 A sequence is called a solution of a recurrence relation


if its terms satisfy the recurrence relation.
 The initial conditions for a sequence specify the terms
that precede the first term where the recurrence
relation takes effect.
Recurrence Relations
Example 1: Let {an} be a sequence that satisfies the
recurrence relation an = an-1 + 3 for n = 1,2,3,4,….
Suppose that a0 = 2.
What are a1 , a2 and a3?
[Here a0 = 2 is the initial condition.]

Solution: We see from the recurrence relation that


a1 = a0 + 3 = 2 + 3 = 5
a2 = 5 + 3 = 8
a3 = 8 + 3 = 11
Recurrence Relations
Example 2: Let {an} be a sequence that satisfies the
recurrence relation an = an-1 – an-2 for n = 2,3,4,….
Suppose that a0 = 3 and a1 = 5.
What are a2 and a3?
[Here the initial conditions are a0 = 3 and a1 = 5. ]

Solution: We see from the recurrence relation that


a2 = a1 - a0 = 5 – 3 = 2
a3 = a2 – a1 = 2 – 5 = –3
Fibonacci Sequence
Definition: Define the Fibonacci sequence, f0 ,f1 ,f2,…, by:
 Initial Conditions: f0 = 0, f1 = 1
 Recurrence Relation: fn = fn-1 + fn-2

Example: Find f2 , f3 , f4 , f5 and f6 .

Answer:
f2 = f1 + f0 = 1 + 0 = 1,
f3 = f2 + f1 = 1 + 1 = 2,
f4 = f3 + f2 = 2 + 1 = 3,
f5 = f4 + f3 = 3 + 2 = 5,
f6 = f5 + f4 = 5 + 3 = 8.
Exercise 1

Solution:
Exercise 2

Solution:
Solving Recurrence Relations
Finding a formula for the nth term of the sequence
generated by a recurrence relation is called solving the
recurrence relation.
1) Need to find the formula by using method of
iteration namely
 Forward substitution
 Backward substitution
2) Then, proving of the formula can be done by using
mathematical induction.
Iterative Method 1: Forward Substitution

Working upward,
Let {an} be a sequence that satisfies the recurrence relation
an = an-1 + 3 for n = 2,3,4,…. and suppose that a1 = 2.
a2 = 2 + 3
a3 = (2 + 3) + 3 = 2 + 3 ∙ 2
a4 = (2 + 2 ∙ 3) + 3 = 2 + 3 ∙ 3
.
.
.
an = an-1 + 3 = (2 + 3 ∙ (n – 2)) + 3 = 2 + 3(n – 1)
Iterative Method 2: Backward Substitution
Working downward,
Let {an} be a sequence that satisfies the recurrence relation an = an-1 + 3 for n =
2,3,4,….
Suppose that a1 = 2.
an = an-1 + 3
= (an-2 + 3) + 3 = an-2 + 3 ∙ 2
= (an-3 + 3 )+ 3 ∙ 2 = an-3 + 3 ∙ 3
= (an-4 + 3 )+ 3 ∙ 3 = an-4 + 3 ∙ 4
=(an-5 + 3 )+ 3 ∙ 4 = an-5 + 3 ∙ 5
=(an-6 + 3 )+ 3 ∙ 5 = an-6 + 3 ∙ 6
.
.
= a4 + 3(n – 4)
= a3 + 3(n – 3)
= a2 + 3(n – 2) = (a1 + 3) + 3(n – 2) = 2 + 3(n – 1)
Guessing Sequences
Example: Conjecture a simple formula for an if the first 10 terms
of the sequence {an} are 1, 7, 25, 79, 241, 727, 2185, 6559, 19681,
59047.
Solution:
1)The ratio of each term to the previous approximates 3.
2)Compare with the sequence 3n .
3)Notice that the nth term is 2 less than the corresponding
power of 3. So a good conjecture is that an = 3n − 2.
Some Useful Summation Formulae
Solving Recurrence Relations
Example: Let a0 , a1 , a2 , … be the sequence of a
recurrence relation defined as follows:
 For all integers k>1 ,
1. ak = ak-1 + 2
2. Initial condition: a0 = 1
Solve the recurrence relation by using iterative
method.
Activity 1: Solve the recurrence relation
by iteration
1.

2.

3.
Activity 1: Solution
1. 2.

3.
Modeling with Recurrence Relations
 Recurrence relation can be used to model a wide
variety of problems.
 Example:
 finding compound interest
 counting rabbits in an island
 determining the number of moves in the Tower of Hanoi
puzzle
 counting bit strings with certain properties.
Example: Financial Application
Suppose that a person deposits $10,000.00 in a savings account
at a bank yielding 11% per year with interest compounded
annually. How much will be in the account after 30 years?
Solution: Let Pn denote the amount in the account after 30
years. Pn satisfies the following recurrence relation:
Pn = Pn-1 + 0.11Pn-1 = (1.11) Pn-1 with P0 = 10,000

Using Forward Substitution


P1 = (1.11)P0
P2 = (1.11)P1 = (1.11)2P0
P3 = (1.11)P2 = (1.11)3P0
:
Pn = (1.11)Pn-1 = (1.11)nP0 = (1.11)n 10,000
Pn = (1.11)n 10,000 (Can prove by induction)
P30 = (1.11)30 10,000 = $228,992.97
Rabbits & Fibonacci Numbers
Example: A young pair of rabbits (one of each gender) is placed on an
island. A pair of rabbits does not breed until they are 2 months old.
After they are 2 months old, each pair of rabbits produces another pair each
month.
Find a recurrence relation for the number of pairs of rabbits on the island
after n months, assuming that rabbits never die.
(This is the original problem considered by Leonardo Pisano (Fibonacci) in
the thirteenth century.)
Rabbits & Fibonacci Numbers (cont.)
Solution: Let fn be the number of pairs of rabbits after n months.
fn-1 , n = 1,2,3,… are the terms of the Fibonacci sequence.

 f1 = 1 pairs of rabbits on the island at the end of the first month.


 f2 = 1 because the pair does not breed during the first month.
 To find the number of pairs on the island after n months, add the
number on the island after the previous month, fn-1, and the
number of newborn pairs, which equals fn-2, because each newborn
pair comes from a pair at least two months old.

Consequently the sequence {fn } satisfies the recurrence relation :


fn = fn-1 + fn-2 for n ≥ 3 with the initial conditions f1 = 1 and f2 = 1.
The number of pairs of rabbits on the island after n months is given by
the nth Fibonacci number.
Tower of Hanoi Puzzle
In the late 19th century, the French mathematician Édouard Lucas
invented a puzzle consisting of three pegs on a board with disks of
different sizes. Initially all of the disks are on the first peg in order of
size, with the largest on the bottom.

Initial Position

Rules: You are allowed to move the disks one at a time from one peg to
another as long as a larger disk is never placed on a smaller.
Goal: Using allowable moves, end up with all the disks on the second
peg in order of size with largest on the bottom.
Tower of Hanoi Puzzle
(continued)

Solution: Let {Hn} denote the number of moves needed to solve the Tower of Hanoi Puzzle
with n disks. Set up a recurrence relation for the sequence {Hn}. Begin with n disks on peg 1.
Transfer the top n −1 disks, following the rules of the puzzle, to peg 3 using Hn−1 moves.
Use 1 move to transfer the largest disk to the second peg. Then, transfer the n −1 disks from
peg 3 to peg 2 using Hn−1 additional moves. This can not be done in fewer steps.
Hence, Hn = 2Hn−1 + 1.
The initial condition is H1= 1 since a single disk can be transferred from peg 1 to peg 2 in one
move.
 Use an iterative approach to solve this recurrence relation by repeatedly expressing Hn in
terms of the previous terms of the sequence.
Hn = 2Hn−1 + 1
= 2(2Hn−2 + 1) + 1 = 22 Hn−2 +2 + 1
= 22(2Hn−3 + 1) + 2 + 1 = 23 Hn−3 +22 + 2 + 1

= 2n-1H1 + 2n−2 + 2n−3 + …. + 2 + 1
= 2n−1 + 2n−2 + 2n−3 + …. + 2 + 1 because H1= 1
= 2n − 1 using the formula for the sum of the terms of a geometric series
Counting Bit Strings
Example 4: Find a recurrence relation and give initial conditions for the number of bit
strings of length n without two consecutive 0s. How many such bit strings are there of length
five?
Solution: Let an denote the number of bit strings of length n without two consecutive 0s.
To obtain a recurrence relation for {an } note that the number of bit strings of length n that do
not have two consecutive 0s is the number of bit strings ending with a 0 plus the number of
such bit strings ending with a 1.

Assume that n ≥ 3.
 The bit strings of length n ending with 1 without two consecutive 0s are the bit strings of length
n −1 with no two consecutive 0s with a 1 at the end. Hence, there are an−1 such bit strings.
 The bit strings of length n ending with 0 without two consecutive 0s are the bit strings of length
n −2 with no two consecutive 0s with 10 at the end. Hence, there are an−2 such bit strings.
We conclude that an = an−1 + an−2 for n ≥ 3.
Bit Strings (continued)
The initial conditions are:
 a1 = 2, since both the bit strings 0 and 1 do not have consecutive 0s.
 a2 = 3, since the bit strings 01, 10, and 11 do not have consecutive 0s, while 00 does.

If the bit length is 5, ie. n=5, we need to obtain a5 . We use the recurrence relation three times to
find that:

 a3 = a2 + a1 = 3 + 2 = 5
 a4 = a3 + a2 = 5+ 3 = 8
 a5 = a4 + a3 = 8+ 5 = 13

Note that {an } satisfies the same recurrence relation as the Fibonacci
sequence. Since a1 = f3 and a2 = f4 , we conclude that an = fn+2 .
Counting the Ways to Parenthesize a
Product
Example: Find a recurrence relation for Cn , the number of ways to parenthesize the product of
n + 1 numbers, x0 ∙ x1 ∙ x2 ∙ ⋯ ∙ xn, to specify the order of multiplication.
For example, C3 = 5, since all the possible ways to parenthesize 4 numbers are

((x0 ∙ x1 )∙ x2 )∙ x3 , (x0 ∙ (x1 ∙ x2 ))∙ x3 , (x0 ∙ x1 )∙ (x2 ∙ x3 ), x0 ∙ (( x1 ∙ x2 ) ∙ x3 ), x0 ∙ ( x1 ∙ ( x2 ∙ x3 ))

Solution: Note that however parentheses are inserted in x0 ∙ x1 ∙ x2 ∙ ⋯ ∙ xn, one “∙” operator remains
outside all parentheses. This final operator appears between two of the n + 1 numbers, say xk and xk+1.
Since there are Ck ways to insert parentheses in the product x0 ∙ x1 ∙ x2 ∙ ⋯ ∙ xk and Cn−k−1 ways to insert
parentheses in the product xk+1 ∙ xk+2 ∙ ⋯ ∙ xn, we have

The initial conditions are C0 = 1 and C1 = 1.


The sequence {Cn } is the sequence of Catalan Numbers. This recurrence relation
can be solved using the method of generating functions; see Exercise 41 in Section
8.4 (Rosen’s book).

You might also like